METODE LATIHAN GAME SITUATION 3V3 TERHADAP PENINGKATAN VO2MAKS PADA PEMAIN FUTSAL TIM ARETY FC - Fadly, Moh. Nur; Himawan, Agus; Widodo, Haryo Mukti; Faisal, Bagus Imam (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to determine the effect of the 3v3 game situation training method on increasing VO2Max in futsal players on the Arety FC team. This study uses an experimental method with a pretest and posttest design. The study population was 17-year-old futsal players from the Arety FC team, and the sample was taken using the purposive sampling method, resulting in 30 samples. The training method used in this study was the 3v3 Game Situation. The VO2Max measurement instrument used the Multistage Fitness Test or Bleep Test. The research instrument is a tool used to collect data systematically. In this study, the instruments used were tests and measurements. Data were collected through pretests and posttests by testing the endurance of players using the bleep test to measure the increase in VO2Max. The data analysis technique used SPSS 21. The results of the Wilcoxon test showed that the Sig value <0.05, so there was a significant effect of the 3v3 game situation training method on increasing VO2Max in futsal players on the Arety FC team.